Foot length as a surrogate maker to identify birth weight - Upadhyay, Nitesh; Ahmed, Minhajuddin (International Journal of Contemporary Pediatrics, 2021)
Background: Gestational age and birth weight is an important predicator for morbidity and mortality in neonates. Aim was to determine the correlation of foot length with birth weight and gestational age in neonates. Methods: This was a prospective observational study done in the neonatal unit department of pediatrics in Chirayu medical college and hospital, Bhopal. There were 1739 deliveries included during the study period from January 2016 to December 2020. Study group comprised of all live born babies delivered in within 24 hours of birth who fulfilled the inclusion criteria. Results: The study comprised of 1739 newborn babies, out of which 896 (51.51%) were males and 843 (48.49%) were females. Male:female ratio 1.06:1. In our study group, 337 (15.6%) babies were preterm and 1385 (84.39%) were of term gestation. We found a positive linear correlation of foot length with all birth weight groups in a newborn with a correlation coefficient (r=0.78) and p<0.001 was found. Similarly, a positive correlation of foot length and gestational age of newborn in both term and preterm babies with (r=0.83) with p<0.01. Foot length has 87.4% sensitivity and 91.7% specificity among low-birth-weight babies with respect to cut off foot length of 75.5 mm. Foot length has 78.7% sensitivity and 63.7% specificity among preterm babies. Conclusions: Foot length can be used as a screening tool to identify low birth weight (LBW) and preterm babies as it had a higher sensitivity and specificity.